THE BEHAVIOR OF RESIDUAL STRESS UNDER CYCLIC THERMO-MECHANICAL LOADS IN AUTOFRETTAGED AND SHRINK-FITTED CYLINDERS - Ossama R. Abdelsalam, (International Journal of Innovations in Engineering Research and Technology, 2021)
The autofrettage and shrink-fit processes are used to create compressive residual stresses at the near bore area to increase the load-bearing capacity of the pressure vessels under thermomechanical loads. In this paper, an investigation of the effect of thermal accumulation due to cyclic thermomechanical loads on the residual stresses created by autofrettage and shrink-fit processes has been revealed. A Fully coupled thermo-elastic finite element model has been developed in ANSYS environment to calculate the temperature, hoop, and equivalent von –Mises stresses profiles through the wall thickness of the cylinder. The finite element model is utilized to illustrate the behavior of the residual stresses after different cyclic regimes of thermomechanical loads considering thermal accumulation. It has been found that relaxation time within 60 seconds as a minimum is crucial after a certain number of thermo-mechanical loads to let the cylinder withstand more thermomechanical cycles